Kompetensi, Beban Kerja dan Kualitas Penyajian Laporan Keuangan di UPT Kementerian LHK Bali - Widnyani, Nyoman Ari; Widanaputra, A.A.G.P (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p17, 2021)
This research was conducted to determine the effect of competence and workload on the quality of financial statement presentation. This research was conducted at 8 UPT Ministry of Environment and Forestry in Bali Province. Determination of the sample using nonprobability sampling is the purposive sampling approach. The analysis technique used is multiple linear regression analysis. The results of this study illustrate that competence has a significant positive effect on the quality of the presentation of financial statements, meaning that the higher the competency possessed, the quality of financial statement presentation increases, while the workload has a significant negative effect on the quality of the presentation of financial statements, meaning that the higher the workload of employees the presentation of financial statements will continue to decline. Keywords: Competence; Workload; Quality of Financial Statement Presentation.